THE IMPORTANCE OF TRANSLATION IN INTELLECTUAL DIALOGUE BETWEEN CIVILIZATIONS - Nazish Safdar; Dr. Farhat Jabeen Virk (Al-Qanṭara, 2023)
Translation is an art in itself and expert book translator should be lauded for opening up a new world for readers around the world. The role of translation has become even more significant in 21st century. As it is the most effective way of building cross culture bridges. In 21st century culture has become mixed, hybrid all over the world. Today the translation is the study of culture and language. Culture has gained paramount importance in translation study. As the demand of translation has soared manifold in this globalization world so the role of translator has become more important. The translator has gained the status of creator so he has to compete with the emerging challenges of 21st century. The cultural interaction can be studied through translation. Cultural connections play an important role in translation studies. As we saw before globalization is a process affecting cultures, economics, societies, nation policies a change in every field. In this situation no nation in the world can achieve the highest end of development without translation because global communication is possible only through translation. Key Words: Translation, literary translations, globalization, mutual dialogue, Gulf War, literature and civilization, inter-cultural dialogue